Porphyromonas gingivalis amount in the tongue biofilm is associated with erosive arthritis in systemic lupus erythematosus. (July 2022) - Ceccarelli, Fulvia; Saccucci, Matteo; Natalucci, Francesco; Olivieri, Giulio; Bruni, Erika; Iacono, Roberta; Colasanti, Tania; Di Carlo, Gabriele; Alessandri, Cristiano; Uccelletti, Daniela; Russo, Paola; Pilloni, Andrea; et al.
Background: Several data have demonstrated the occurrence of erosive arthritis in Systemic Lupus Erythematosus (SLE) patients. However, a few studies have focused on the pathogenic mechanisms involved in this feature. The implication of oral pathogens has been proved in Rheumatoid Arthritis: in particular, Porphyromonas gingivalis ( Pg ), by inducing citrullination, could trigger autoimmune response. Here, we evaluated amount of Pg on the tongue in a cohort of SLE patients with arthritis, focusing on the association with the erosive phenotype. Methods: SLE patients with arthritis were enrolled. DAS28 was applied to assess activity. Erosive damage was evaluated by ultrasound at level of MCP (metacarpophalangeal) and PIP (proximal interphalangeals) joints. All subjects underwent a tongue cytologic swab in order to quantify the amount of Pg (real-time PCR). The bacterium expression was obtained from the ratio between the patient's DNA amount and that obtained from healthy subjects. Results: 33 patients were enrolled (M/F 3/30; median age 47 years, IQR 17; median disease duration 216 months, IQR 180): 12 of them (36.4%) showed erosive damage, significantly associated with ACPA positivity ( p = 0.03) and higher values of DAS28 ( p = 0.01). A mean ratio of 19.7 ± 31.1 was found for Pg amount. Therefore, we used Pg mean values as threshold, identifying two groups of patients, namely, high Pg and low Pg. Erosive damage was significantly more frequent in high Pg patients in comparison with low Pg (60.0% vs 26.0%, p = 0.001). Furthermore, high Pg patients showed higher prevalence of skin manifestations, serositis, and neurological involvement ( p = 0.005, p = 0.03, p = 0.0001, respectively). Conclusion: The possible contribution of oral microbiota in SLE erosive arthritis was here evaluated for the first time, finding a significant association between erosive damage and higher expression of Pg at tongue level.